Zabytkowy park w Niekarzynie - próba określenia granic ochrony konserwatorskiej parku = Historic park in Niekarzyn. An attempt at determining the borders of the park and thus the borders of conservation protection - Eckert, Wojciech (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents a description of the park complex in Niekarzyn, which is listed in the historic register of monuments in the Lubuskie Province. The park is currently run down. Thus far, historical research on the park has not been carried out, and the tree stand has not been cataloged. In order for it to be effectively covered by conservation protection, it is necessary to establish the borders of the park.
Keywords: park w Niekarzynie; krajobraz kulturowy; rejestr zabytków; park in Niekarzyn; register of historic monuments; cultural landscape